UV Shielding Properties of Cellulose/TiO2 Composite Film - Plermjai, Kittiya; Phoohinkong, Weerachon; Pavasupree, Sorapong; Mekprasart, Wanichaya; Pecharapa, Wisanu; Boonyarattanakalin*, Kanokthip (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
Cellulose/TiO2 composite film was prepared for UV shielding applications. Cellulose was extracted from sugarcane bagasse by ball milling process. The cellulose/ TiO2 composite film with different concentrations of cellulose showed a synergic feature of optical transparency and UV-blocking. The crystalline structure of cellulose was characterized by X-ray diffraction (XRD). The treated cellulose has higher crystallinity than the untreated cellulose. Fourier transform infrared spectroscopy ( FTIR) analysis shows the evidence of chemical treatment hemicellulose and lignin removal from sugarcane bagasse. The optical properties were measured by UV- Vis spectrometer, the results of TiO2 and cellulose solution correspond to UV- A and UV- C absorbance regions with high transparent of cellulose composite films. The revealed results are essential for UV protecting materials application. Keywords: nanocellulose composite, TiO2, UV-shielding, ball milling *Corresponding author: E-mail: kanokthip.bo@kmitl.ac.th